Seroprevalence and detection of bovine leukosis virus in semen from breeding bulls in Costa Rica - Chacón Calderón, Jorge (2023)
Bovine leukemia virus (BLV) causes enzootic bovine leukosis, a persistent infection and the most important neoplastic disease in cattle. It is spread primarily by transferring infected lymphocytes through blood from carriers to healthy animals. The present study is aimed at determining the seropositivity of BLV in breeding bulls from Costa Rica and at detecting for the frst time in the country BLV DNA in bull semen. Between May 2011 and August 2018, 379 blood and 133 semen samples were collected from bulls distributed in 118 farms. The serum was analyzed by an enzymatic immunoassay and the semen by polymerase chain reaction and sequencing. BLV seropositivity was 43.5% (165/379), while 64.4% (76/118) of the farms had positive reactors. Holstein (75.7%) and Jersey (73.0%) breeds showed the highest seropositivity. In addition, Bos taurus bulls (68.1%), older than seven years (50.0%), and those belonging to dairy farms (75.5%) had higher seropositivity compared to Bos indicus (17.7%), younger than seven years (42.2%), and those from beef farms (15.5%), respectively. Moreover, Bos taurus bulls had a higher risk of being seropositive than Bos indicus (OR=3.4; 95% CI: 1.7–6.8). BLV DNA was found in one semen sample (2.5%; 1/40) from a seropositive bull. The importance of serum and molecular BLV screening in semen samples and the potential role of some risk factors associated with the disease, such as the bull’s age, genotype, and type of livestock productive system, is argued in the present report.